Groups VII. (London : Waddington Galleries, 1983)
Arp, Jean ; Avery, Milton ; Baselitz, Georg ; Blake, Peter ; Bonnard, Pierre ; Calder, Alexander ; Caro, Anthony ; Caulfield, Patrick ; Chagall, Marc ; Craig-Martin, Michael ; Dali, Salvador ; Dibbets, Jan ; Dine, Jim ; Dubuffet, Jean ; Dufy, Raoul ; Flanagan, Barry ; Francis, San ; Frink, Elisabeth ; etc.
Groups VII, Waddington Galleries, London, 5 January - 28 January 1984
boek